2014
DOI: 10.1039/c4ra06168c
|View full text |Cite
|
Sign up to set email alerts
|

Eu3+and Tb3+doped LaPO4nanorods, modified with a luminescent organic compound, exhibiting tunable multicolour emission

Abstract: Co-precipitation reaction followed by hydrothermal treatment were used to synthesise Eu 3+ or Tb 3+ doped LaPO 4 nanorods, of 5-10 nm in width and 50-100 nm in length. Surface modification of the as-prepared nanoparticles with a selected luminescent organic compound resulted in formation of hybrid inorganicorganic nanomaterials. The products obtained exhibited tunable multicolour luminescence, dependent on the surface modification and applied excitation wavelength. The colour of their emission can be altered f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
24
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 55 publications
(24 citation statements)
references
References 49 publications
0
24
0
Order By: Relevance
“…The observed strong infrared band of OH revealed that abundant OH groups in H 2 O exist on the surface of nano‐products, and play a key role in their solubility, colloidal stability, and conjugation with bio‐macromolecules. Observed characteristic infrared peaks at 1047, 613 and 536 cm −1 were assigned to the stretching and bending vibrational modes of the phosphate (PO 4 3− ) group . Silica surface modification of the surface of the core/shell NRs was confirmed by characteristic silica peaks of silica at 1080, 603, 515, and 463 cm −1 , which can be assigned to Si–O–Si, Si–OH, and Si–O stretching and bending vibrations modes of surface functionalized amorphous silica .…”
Section: Resultsmentioning
confidence: 86%
See 2 more Smart Citations
“…The observed strong infrared band of OH revealed that abundant OH groups in H 2 O exist on the surface of nano‐products, and play a key role in their solubility, colloidal stability, and conjugation with bio‐macromolecules. Observed characteristic infrared peaks at 1047, 613 and 536 cm −1 were assigned to the stretching and bending vibrational modes of the phosphate (PO 4 3− ) group . Silica surface modification of the surface of the core/shell NRs was confirmed by characteristic silica peaks of silica at 1080, 603, 515, and 463 cm −1 , which can be assigned to Si–O–Si, Si–OH, and Si–O stretching and bending vibrations modes of surface functionalized amorphous silica .…”
Section: Resultsmentioning
confidence: 86%
“…The observed sharp transitions corresponded to the direct excitation of Eu 3+ from the ground state to the excited state arising from the 4 f manifold. Among the observed excitation peaks, the 7 F 0 → 5 L 6 transition at 393 nm was the most prominent and showed the greatest sensitivity in the spectrum …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Eu 3 þ -red, Tb 3 þ -green) [8,[21][22][23]. They reveal also long luminescence lifetimes (several ms), narrow emission bands and a photostability [22,24,25].…”
Section: Introductionmentioning
confidence: 99%
“…They can exhibit simultaneously two or more functionalities, namely tuneable multicolor luminescence, magnetic response, plasmonic properties, biological activity, drug-delivery capability, catalytic activity, etc. [8][9][10][11][12][13][14]. The multifunctionality and possibility of alterations of their properties are crucial factors promoting development of such nanocomposites and hybrid nanomaterials.…”
Section: Introductionmentioning
confidence: 99%